Elaboration and validation of a booklet on diabetes for Community Health Workers - Stefãne Amorim Ribeiro; Alexandra Dias Moreira; Janice Sepúlveda Reis; Aleida Nazareth Soares; Tatiane Géa-Horta (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to develop and validate a diabetes booklet for Community Health Workers. Methods: methodological study developed in seven steps: Bibliographic review; Development of the booklet; Calculation of readability and comprehensibility scores; Validation of the booklet by the committee of judges; Discussion between experts; Validation of the booklet by the target audience; and Final discussion between experts. Validation was performed by 10 judges via e-Surv and on a face-to-face test with 5 Community Health Workers, considering the minimum Content Validity Coefficient of 0.80. Results: the booklet had a mean Content Validity Coefficient of 0.97 in the validation by the committee of judges, and the images had 96.67% approval. In the face-to-face test, the Community Health Workers considered the material clear and appropriate to the function. Conclusions: the booklet was developed and validated on its content and relevance, and it can be used by Community Health Workers for diabetes education.